Использование метода проектов в преподавании дисциплин естественного цикла в лицее Белорусского национального технического университета - Гвоздовская, Е. В. (БНТУ, 2011)
The article is about the introduction of the project method of learning of the pupils of the lyceum of BNTU within the scope of teaching of natural disciplines and its role in the formation of ecological consciousness of specialists in technical engineering.